Atomically dispersed Fe–Nx active sites within hierarchical mesoporous carbon as efficient electrocatalysts for the oxygen reduction reaction. Issue 35 (23rd August 2019) - Gu, Wenling; Wu, Maochun; Sun, Jing; Xu, Jianbo; Zhao, Tianshou
Abstract : A novel protocol for synthesis of high performance N-doped hierarchically porous graphitic carbon electrocatalysts with single Fe atoms by pyrolyzing a mesoporous Fe–polydopamine precursor without an extra template removal process. Abstract : It is still a great challenge to develop highly efficient catalysts with earth abundant materials to replace the precious platinum group metal (PGM) catalysts for the oxygen reduction reaction (ORR). Here, we report a self-sacrificing template strategy to synthesize hierarchical mesoporous carbon materials with atomically dispersed Fe–N x active sites. Derived from an Fe–polydopamine precursor obtained via in situ polymerization of dopamine and etching of a cobalt template using an FeCl3 solution, the resultant catalyst shows a high specific surface area (1229.3 m 2 g −1 ), a hierarchical mesoporous structure, an improved hydrophilicity, and abundant atomically dispersed Fe–N x active sites. As a result, the single atom catalyst exhibits a remarkable activity and durability in 0.1 M KOH with an onset and half-wave potential of 1.03 and 0.88 V, respectively, which surpass those of its commercial Pt/C counterpart. In acidic and neutral media, the catalyst also exhibits a comparable electrocatalytic activity to but much greater durability than commercial Pt/C. This work opens a new avenue for synthesis of cost-effective catalysts at the atomic scale for efficient energy conversion.